A comparative analysis of Namibia’s peacemaking role in the Southern African Development Community region : the case of the Democratic Republic of Congo and Angola - Amupanda, Job Shipululo Kanandjembo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.